PROJECT-BASED APPROACH IN IMMERSED MODEL TO IMPROVE TEACHERS' COMPETENCE IN DESIGINING LEARNING - Angraeny Unedia Unedia (Universitas Muhammadiyah Ponorogo, 2018)
This research aimed to improve the competence of PAUD teachers in providing instruction. This research used Classroom Action Research model by Kemmis and Taggart. The subjects involved in this research were participants who were involved in the model research with immersed model in Situbondo Regency, East Java. The Immersed Model is one of integrated curriculums developed by Fogarty which is based on how to involve students' abilities by combining more than one developmental aspect to see children able to do their own activities with fun and reshape new concepts in their own way. Implementation framework of this immersed model is a large theme that reflects students' abilities. In this research, the theme framework is about introducing early childhood learning that focuses on constructing insights into natural and environmental love for early childhood, one of which is introducing the volunteer in flood prevention for early childhood.